2022
DOI: 10.1007/s12011-022-03168-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Promote Osteoplastic Precursor Differentiation by Activating the Wnt Pathway

Abstract: Osteoplastic precursors are critical for fracture repair and bone homeostasis maintenance. Cerium oxide nanoparticles (CeO2 NPs) can promote the osteogenic differentiation of mesenchymal stem cells and secrete vascular endothelial growth factors. However, little is known about its role in precursor osteoblasts; therefore, we further investigated the effect and mechanism of CeO2 NPs in precursor osteoblasts. Cell counting kit-8 analysis was utilized to detect the toxicity of CeO2 NPs on MC3T3-E1 mouse osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(25 reference statements)
2
18
0
Order By: Relevance
“…The early induction of differentiation of hPDLCs cultured with the ART-loaded SiCaCe NPs, as indicated by the increased ALP activity in day 14, and is followed by a decrease in ALP activity after 21 days in culture, during mineral deposition. Our results agree with the studies from Stein and Lian, and Choi et al, who showed that the peak of ALP expression was observed during the post-proliferative period, and cells stained positive for ALP during the early mineralization stage, were followed by the decreased ALP expression during the heavy mineralization stage [ 43 , 44 ]. Assessment of the ALP expression at the mRNA level might show the peak expression at an earlier timepoint [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The early induction of differentiation of hPDLCs cultured with the ART-loaded SiCaCe NPs, as indicated by the increased ALP activity in day 14, and is followed by a decrease in ALP activity after 21 days in culture, during mineral deposition. Our results agree with the studies from Stein and Lian, and Choi et al, who showed that the peak of ALP expression was observed during the post-proliferative period, and cells stained positive for ALP during the early mineralization stage, were followed by the decreased ALP expression during the heavy mineralization stage [ 43 , 44 ]. Assessment of the ALP expression at the mRNA level might show the peak expression at an earlier timepoint [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, Ce-NPs bioactivity and ability to reduce ROS should not be solely attributed to its redox states, but can also be related to components of Ce-NPs surface chemistry, such as particle morphology and surface modification [ 43 ]. Luo et al demonstrated that Ce-NPs promoted the differentiation of precursor osteoblasts by enabling the nuclear translocation of β-catenin protein and activation of the Wnt pathway [ 44 ]. Lu et al showed that incorporation of Ce-NPs in hollow mesoporous bioglass scaffolds activates the ERK pathway, thus stimulating the osteogenic differentiation of bone marrow MSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These unique XRD peaks were defined by their respective indices (111), ( 200), (220), (311), ( 222), (400), and (420). 40,41 The diffraction peaks of Gel and Alg mixed with nCeO 2 broadened significantly and moved to lower 2θ. The addition of GA caused the peaks of the GA-nCeO 2 hydrogel to weaken at the first peak while enhancing the second peak, indicating a phase transition during the composite process.…”
Section: Characterization Of Ga-nceo 2 Hydrogel Scaffoldmentioning
confidence: 99%
“…The addition of CeO 2 NPs displays protective effect toward oxidative stress in bone defects. More importantly, CeO 2 NPs have been reported to promote proliferation and osteogenic and adipogenic differentiation of different mesenchymal stem cells and osteoblasts. Under inflammatory conditions, CeO 2 NPs can also regulate the polarization of macrophages and reduce the inflammation expression . Nevertheless, the application of CeO 2 NPs in bone regeneration area is still in its infancy, and multifunctional application scenarios, systematic research, and mechanism studies are of great urgency.…”
Section: Introductionmentioning
confidence: 99%